Social Resilience to Flooding in Vancouver: The Issue of Scale - Chu, Samantha Hao Yiu; Tan, Su-Yin; Mortsch, Linda (Environmental hazards, 2021)
Socioeconomic characteristics are commonly used as indicators of vulnerability and resilience to inform disaster risk planning and management. Vancouver is a coastal seaport city along the west coast of Canada and is exposed to risk from the impacts of flooding. Previous studies have assessed and modelled a city's resilience to environmental hazards based on socioeconomic status derived from census data, such as income status, family structure, and dwelling conditions. However, these data sources are aggregated into different census units of varying scale, such as Census Tracts (CT) and Dissemination Areas (DA). Spatial analysis of the same data using different aggregation units manifests in the Modifiable Areal Unit Problem (MAUP), where varying scale can produce different results and conclusions. This exploratory analysis of the MAUP demonstrates that social resilience to flooding hazards in Vancouver at the CT and DA census scales can have contradictory results depending on the census scale adopted. The effect of scale and the aggregation units at which spatial analysis occurs can have a significant impact on the conclusions imparted and decision making to identify priority areas. Since individual-level disaggregate data is unavailable, the analytical results based solely on aggregate data should be interpreted with caution.